ANALISIS PENERAPAN COATING PADA BAJA ASTM A36 DENGAN VARIASI CAT TERHADAP LAJU KOROSI, KEKUATAN ADHESI DAN KETAHANAN IMPACT COATING - Budiarto, Untung; Manik, Parlindungan; Kusuma, Ghiyats Abiyyu (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
Corrosion is the most common damage experienced by steel structures due to the interaction between a metal and a corrosive environment. One way to prevent corrosion of steel is coating. A good coating must have a low corrosion rate, high adhesion, and material resistance to impact. This study aimed to compare the corrosion rate, adhesion strength, and impact coating values of the different types of paint between epoxy, alkyd, and polyurethane on A36 steel. The type of steel used in this study is ASTM A36 steel. In this study, the type of coating paint used varied. The types of coatings used are epoxy, alkyd, and polyurethane. Aluminum oxide with a mesh size of 24 is used as an abrasive material. Testing the corrosion rate using the electrochemical method, the test used to determine the adhesive power value using the pull off test method, and to determine the coating resistance value using the impact test method. This type of polyurethane coating has the most optimal value between epoxy and alkyd with a corrosion rate value of 9.09×10-5mmpy, an adhesion value of 15.06 MPa, and an impact coating resistance of 4.70 Joules. Based on the results obtained in this study, the different types of coatings affect the value of corrosion rate, adhesion, and impact.